Resolusi Sengketa Kolektif Di Bidang Pertanahan Dalam Perspektif Hukum Dan Sosial - Muhammad Arif Setiawan (Fakultas Hukum Universitas Islam Indonesia, 2006)
There are various choice of alternative communal dispute resolution modees in land dispute. In fact, the implementation of positive legal approach isnotthe only instrument to settle thedispute. Sometimes, the positive legal approach may. raise opposition which triggers a stringent measures which come from the marginal society andcome from the authority holders.